1997
DOI: 10.1136/gut.40.6.739
|View full text |Cite
|
Sign up to set email alerts
|

Gastric mucosal secretion of interleukin-10: relations to histopathology, Helicobacter pylori status, and tumour necrosis factor-alpha secretion.

Abstract: Background-Interleukin-10 (IL-10) is an 18 kDa peptide with a range of antiinflammatory and immunosuppressive properties. Aim-To determine whether this cytokine is involved in gastric mucosal inflammation in Helicobacterpylori infection.Methods-The production of IL-10 by antral mucosal biopsy specimens during short term in vitro culture was determined by measuring IL-10 content of supernatants by enzyme linked immunosorbant assay (ELISA). H pyloon status was determined by serology and histology, with gastritis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
79
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 27 publications
11
79
1
Order By: Relevance
“…Such fact may be due to the production of interleukin-10 (IL-10) that along with the tumor necrosis factor (TNF)-alpha are increased in H. pylori infections (2) . IL-10 may be a protective factor in limiting the tissue damage caused by inflammation that can contribute; however, to a failure of the immune response to eliminate the organism (2) , thus, great concentrations of H. pylori could inhibit the proliferation of mononuclear cells and stimulate a more intense compensatory inflammatory response at the expense of polymorphonuclear cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such fact may be due to the production of interleukin-10 (IL-10) that along with the tumor necrosis factor (TNF)-alpha are increased in H. pylori infections (2) . IL-10 may be a protective factor in limiting the tissue damage caused by inflammation that can contribute; however, to a failure of the immune response to eliminate the organism (2) , thus, great concentrations of H. pylori could inhibit the proliferation of mononuclear cells and stimulate a more intense compensatory inflammatory response at the expense of polymorphonuclear cells.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows the combination of histopathological findings, and Table 2 shows their combining frequency in the same biopsy related to the presence and concentration of H. pylori. (2) . However, some studies have reported that such isolated or combined histological findings have neither sensitive nor specific values enough to predict the diagnosis of this bacterium, and more specific techniques may be required for H. pylori detection as Giemsa staining or Warthin-Starry silver impregnation technique (16,18) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this intention, we crossed IgA-onto IL-10-deficient C57BL/6 mice and obtained double and single gene knockout mice, IL-10 Ϫ/Ϫ /IgA Ϫ/Ϫ and IL-10 Ϫ/Ϫ /IgA ϩ/ϩ . Our choice of the IL-10 Ϫ/Ϫ mice was based on previous studies showing that these mice develop severe gastritis and that IL-10 is strongly produced in the gastric mucosa of patients as well as in mice infected with H. pylori (20,(25)(26)(27)(28)(29)(30)(31)(32). Also,…”
Section: Nfection Withmentioning
confidence: 99%
“…11 In this sense, it is noteworthy that the polymorphism in the genes encoding interleukins (IL) 1β, 1RN, 6, 8 and 10 are associated with increased susceptibility to gastric diseases. [12][13][14][15][16][17] The combined presence of environmental factors, such as, household crowding, inadequate eating habits, low socioeconomic conditions, poor hygienic, excessive alcohol consumption and smoking are related with H. pylori infection, especially when one takes into account aggravation of mucosal damage once the gastric infection with H. pylori induces the mucosal production of various pro-and anti-inflammatory cytokines in the host. The harmful role of environmental factors is related to poor socioeconomic conditions, salt intake, smoking and alcohol consumption.…”
Section: -9mentioning
confidence: 99%